Metal oxides as photocatalysts - Mohammad Mansoob Khan (Journal of Saudi Chemical Society)
Metal oxides are of great technological importance in environmental remediation and electronics because of their capability to generate charge carriers when stimulated with required amount of energy. The promising arrangement of electronic structure, light absorption properties, and charge transport characteristics of most of the metal oxides has made possible its application as photocatalyst. In this article definition of metal oxides as photocatalyst, structural characteristics, requirements of the photocatalyst, classification of photocatalysts and the mechanism of the photocatalytic process are discussed.